Learning Theories An Educational Perspective
The text focuses primary emphasis on cognitive theories that stress learners’ constructions of beliefs, skills, strategies, and knowledge. Behavioral views are also discussed. Following an introductory chapter on learning that discusses key learning issues and historical perspectives, the second chapter discusses conditioning theories of learning. The next five chapters discuss cognitive theories and processes of learning: social cognitive theory, cognitive information processing theory, cognitive learning processes, constructivist theory, and cognition and instruction. The next four chapters cover the key topics of development and learning, neuroscience of learning, content-area learning, and motivation. The concluding chapter asks readers to examine their beliefs about learning, fit these with existing theories, and determine how to apply learning principles to improve teaching and learning. Chapters have numerous applications that apply learning principles to real-world settings. By blending theory, research, and applications throughout, the text provides instructors and students with a unified view of learning in educational settings.